RECENSIONES - Bíblica, Revista (Revista Bíblica, 2019)
S. Scholz (ed.), Feminist Interpretation of the Hebrew Bible in Retrospect (3 vols.) (Pablo R. Andiñach); D. J. Armitage, Theories of Poverty in the World of the New Testament (Edgar A. Toledo Ledezma); A. Puig, Diez textos gnósticos. Traducción y comentario (Alberto C. Capboscq).